2004
DOI: 10.1002/chin.200418105
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole Derivatives as New Potent and Selective 20‐HETE Synthase Inhibitors.

Abstract: Selective 20-HETE Synthase Inhibitors. -Synthesis and 20-HETE synthase inhibitor activity of a variety of N-arylimidazole derivatives are reported. Especially (IIIe) shows potent and selective inhibitory activity. -(NAKAMURA*, T.; KAKINUMA, H.; UMEMIYA, H.; AMADA, H.; MIYATA, N.; TANIGUCHI, K.; BANDO, K.; SATO*, M.; Bioorg. Med. Chem. Lett. 14 (2004) 2, 333-336; Med. Res. Lab.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…The appearance of medium bands at 3696.2 cm À1 in the IR spectra of compound 17 indicated the presence of a free OH in the carboxylic acid group of 2-substituted benzene. Further, the appearance of strong C]O stretching bands at 1695-1670 cm À1 in the IR spectra of (substituted phenyl)-[2-(substituted phenyl)-imidazol-1-yl]-methanones (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) demonstrated the presence of tertiary amide linkage between substituted benzoic acid and imidazole nucleus. Compounds 23 and 25 showed C-Br stretching at 522.8 cm À1 and 533.8 cm À1 , which confirms the presence of 2-bromo substituted benzene ring.…”
Section: Chemistrymentioning
confidence: 96%
See 3 more Smart Citations
“…The appearance of medium bands at 3696.2 cm À1 in the IR spectra of compound 17 indicated the presence of a free OH in the carboxylic acid group of 2-substituted benzene. Further, the appearance of strong C]O stretching bands at 1695-1670 cm À1 in the IR spectra of (substituted phenyl)-[2-(substituted phenyl)-imidazol-1-yl]-methanones (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) demonstrated the presence of tertiary amide linkage between substituted benzoic acid and imidazole nucleus. Compounds 23 and 25 showed C-Br stretching at 522.8 cm À1 and 533.8 cm À1 , which confirms the presence of 2-bromo substituted benzene ring.…”
Section: Chemistrymentioning
confidence: 96%
“…General procedure for the synthesis of (substituted phenyl)-[2-(substituted phenyl)-imidazol-1-yl]-methanones (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) A solution of 2-(substituted phenyl)-1H-imidazoles (1-12) (0.002 mol) in diethyl ether (50 ml) was added to a solution of corresponding substituted benzoyl chloride (0.002 mol) in diethyl ether (50 ml). The above mixture was stirred for 24 h at room temperature.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the inhibition of 20-HETE is now considered as promising new target treatment of renal and cerebrovascular diseases. In continuation of their efforts in search of 20-HETE inhibitors, Nakamura et al (2004) synthesized imidazole-based compounds and found that [6-(4-imidazol-1-yl-phenoxy)-hexyl]dimethyl amine 25 exhibited strong inhibitory activity against 20-HETE synthase with an IC 50 value of 8.8 nM and more than 180-fold to over 15,000-fold selectivity toward CYP1A2, 2C9, 2C19, 2D6, and 3A4.…”
Section: Imidazoles As Carbonic Anhydrase Activatorsmentioning
confidence: 99%